Abusive Supervision, Psychological Capital, and Turnover Intention: Evidence from Factory Workers in China / Supervisión abusiva, capital psicológico e intención de dejar el empleo: estudio de la situación de trabajadores de fábrica en China - Seo, Yumi; Chung, Sun Wook (Relations industrielles / Industrial Relations, 2019)
As a dark side of leadership, scholars have shown that abusive supervision (AS) has negative consequences for subordinates work, organizations and society. This study focuses on the detrimental effects of AS on employee turnover intention, which is one of the major concerns for firms in China. We examined the underlying psychological mechanism between AS and turnover intention, specifically by focusing on the mediational role of psychological capital (Luthans et al., 2007) based on the conservation of resources theory (COR, from Hobfoll, 2002). By explaining the process of how AS can deplete individuals’ resources, which leads to protective behaviour and attitudes, we attempt to integrate COR theory into the existing AS literature. We also investigated the moderating role of broader organizational contexts represented by organizational justice perception in the relationship between AS and turnover intention, showing boundary conditions where the effects of AS can be amplified with regard to overall organizational justice perception.Based on survey data collected from young factory workers in northern China, this study finds that abusive supervision is positively correlated with turnover intention. Psychological capital, especially optimism, mediates this relationship. In addition, when workers perceived high levels of procedural and distributive organizational justice, this association between abusive supervision and turnover intention was even stronger. Furthermore, the perception of procedural organizational justice also moderated the mediation mechanism of optimism between abusive supervision and turnover intention.This paper enriches the extant studies by considering the relationship between abusive supervision and its negative consequences for manufacturing workplaces in a non-western country, a context that has been little studied. In addition, by showing how psychological capital and the perception of organizational justice affect the AS-turnover intention relationship, this paper provides a nuanced and deeper understanding of the psychological mechanism and organizational context of abusive supervision.